2018
DOI: 10.1021/acsami.7b15034
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex-Forming Cohost for High Efficiency and High Stability Phosphorescent Organic Light-Emitting Diodes

Abstract: An exciplex forming cohost system is employed to achieve a highly efficient organic light-emitting diode (OLED) with good electroluminescent lifetime. The exciplex is formed at the interfacial contact of a conventional star-shaped carbazole hole-transporting material, 4,4',4″-tris(N-carbazolyl)-triphenylamine (TCTA), and a triazine electron-transporting material, 2,4,6-tris[3-(1H-pyrazol-1-yl)phenyl]-1,3,5-triazine (3P-T2T). The excellent combination of TCTA and 3P-T2T is applied as the cohost of a common gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 40 publications
(76 reference statements)
4
49
0
Order By: Relevance
“…The PLQYs of the exciplex-basedf ilms are comparable to those of the Bebq 2 -basedf ilms, and the t PL values are slightly longer,w hich is likelyt ob edue to delayed energy transfer from the exciplex causedb yt he additional intersystem crossing (ISC) and reverse intersystem crossing (RISC) processes before energy transfer ( Figure S4 and Ta ble S2 in the Supporting Information). [15] To confirm the utility of the TCTA:PIM-TRZ exciplex system as the cohost for 1F-Ir/2F-Ir and gain an insight into the influence of host material on device performance, OLEDs with structures of ITO/TAPC (40 nm)/TCTA( 10 nm)/TCTA:PIM-TRZ:x wt % 1F-Ir or 2F-Ir (30 nm)/PIM-TRZ (60 nm)/LiF( 1nm)/Al (100 nm) were then fabricated. Besides workinga st he components of the cohost,T CTAa nd PIM-TRZ also worked as carrier transporting layers.…”
Section: Resultsmentioning
confidence: 99%
“…The PLQYs of the exciplex-basedf ilms are comparable to those of the Bebq 2 -basedf ilms, and the t PL values are slightly longer,w hich is likelyt ob edue to delayed energy transfer from the exciplex causedb yt he additional intersystem crossing (ISC) and reverse intersystem crossing (RISC) processes before energy transfer ( Figure S4 and Ta ble S2 in the Supporting Information). [15] To confirm the utility of the TCTA:PIM-TRZ exciplex system as the cohost for 1F-Ir/2F-Ir and gain an insight into the influence of host material on device performance, OLEDs with structures of ITO/TAPC (40 nm)/TCTA( 10 nm)/TCTA:PIM-TRZ:x wt % 1F-Ir or 2F-Ir (30 nm)/PIM-TRZ (60 nm)/LiF( 1nm)/Al (100 nm) were then fabricated. Besides workinga st he components of the cohost,T CTAa nd PIM-TRZ also worked as carrier transporting layers.…”
Section: Resultsmentioning
confidence: 99%
“…For serving as host, the exciplex system must satisfy certain conditions such as (i) T 1 level of the exciplex has to be lower compared to the individual counterparts for the confinement of the excitation energy within the exciplex state, and (ii) T 1 level of the exciplex has to be higher than that of the dopant for confining the emission solely on the emissive dopants, ( carbazole hole-transporting material, TCTA, and a triazine electron-transporting material, 3P-T2T for a green phosphorescent emitter, Ir(ppy) 2 (acac) to achieve an OLED with high efficiency and very good electroluminescent lifetime. 10 The device fabricated with this system was found to display maximum external quantum efficiency of 29.6%, power efficiency of 147.3 lm/W, and current efficiency of 107 cd/A. For a comparative study, two devices, D1 and D2 were studied and their electroluminescent performances are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In this interface, sufficient charge accumulation occurred owing to large energy-level offsets, and thus, efficient exciplex exciton formation resulted in the EML. 10 The molecular structures used in this study are shown in Figure 3 and the device data summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the driving voltage can be greatly reduced and the exciton recombination zone can also be significantly broaden, thus enhancing the PE and alleviating the efficiency roll‐off. At present, the monochromatic OLEDs based on exciplexes as hosts of phosphors have achieved the higher EQE over 30% 5c,7a,8. However, there is still no good report on the preparation of high efficiency white OLEDs (WOLEDs) with exciplexes as hosts due to the difficulty of matching between exciplex hosts and different phosphor guests 5b,9…”
Section: Summary Of the Key El Parameters For The Fabricated Devices mentioning
confidence: 99%